Low power technology for wearable cognition systems - Yates,DC; Casson,AJ; Rodriguez-Villegas,E (SPRINGER-VERLAG, 2007)
This paper analyses a key tradeoff behind miniature devices intended to monitor cognition-related parameters. These devices are supposed to be worn by people that would otherwise be carrying on a normal life and this factor imposes important constraints in the design. They have to be wireless, wearable, discrete, low maintenance and reliable. In order to reduce power intelligence will be built into the sensors aiming to reduce the data transmission to only that information that it is strictly necessary. This intelligence will be in the form of an algorithm which will be required to be implemented in electronic circuits as part of the system. The complexity of the algorithm affects the complexity of the electronics and hence the power consumption. This, in turn affects the size of the battery and the overall size of the device. For the sensor to be low maintenance the device must operate for extended periods from the battery, adding more constraints to the power consumption of the electronic circuits. The battery must be kept small so that the overall size of the device is small and lightweight enough to be worn on the body and the more discrete the device the higher consumer compliance. A tradeoff has to be met between the algorithm complexity, the power consumption of the electronics required to realize the latter, the power consumption required to transmit data and the battery size and lifetime.